Phase-selective and photoactivity investigation of solvothermal synthesized Cu2ZnSnS4 nanoparticles. (5th February 2016) - Zhang, Qing; Cao, Meng; Gao, Wang Sheng; Yang, Jin; Shen, Jie Sheng; Huang, Jian; Sun, Yan; Wang, Lin Jun; Shen, Yue
Abstract: Cu2 ZnSnS4 (CZTS) nanoparticles with bandgap of about 1.5 eV were synthesized by a simple solvothermal method with oleylamine (OAm) and ethanediamine (En) as the reaction solvents. Raman spectra and X-ray photoelectron spectroscopy examined the phase purities of CZTS nanoparticles. Kesterite structured CZTS were gradually changed into the wurtzite structured CZTS by varying the volume ratios of OAm and En, which was confirmed by X-ray diffraction measurements. Time-dependent experiments were performed to study the mechanism of the phase selection of CZTS, which indicated that En played an important role in the formation of wurtzite structured CZTS. Annealing process improved the crystallinities of CZTS nanoparticle thin films, but wurtzite structured CZTS was changed to more stable kesterite phase. Photo-electrochemical measurement indicated that wurtzite structured CZTS nanoparticle thin films had better photoelectric properties. Graphical abstract: Cu2 ZnSnS4 (CZTS) nanoparticles were synthesized by a simple solvothermal method and photo-electrochemical measurements of spin coated CZTS thin films indicated that wurtzite structured CZTS had better photoelectric properties. Highlights: Structural controlled Cu2 ZnSnS4 nanoparticles were synthesized by solvothermal method. The reaction rate of Zn 2 + with sulfur precursors determined the structure of Cu2 ZnSnS4. Cu2 ZnSnS4 nanoparticles synthesized with ethanediamine have better optoelectronic properties.